Assessment of the Economic, Social and Environmental Dimensions of the Indicators for Sustainable Development. (23rd November 2016) - Strezov, Vladimir; Evans, Annette; Evans, Tim J.
Abstract: Nine different indices for measuring sustainable development, comprising Change in Wealth Index (CWI), Ecological Footprint (EF), Environmental Performance Index (EPI), Environmental Sustainability Index (ESI), Genuine Savings Index (GSI), Global Well‐Being Index (GWI), Happy Planet Index (HPI), Human Development Index (HDI) and Sustainable Society Index (SSI) were selected in this study. The indices were analysed for their ability to measure the economic, environmental and social dimensions of sustainable development. Only two indices (SSI and GSI) considered all three dimensions of sustainable development, while the remaining measured either the socio‐economic, socio‐environmental or just economic and environmental dimensions. A normalized average sustainability index (NASI) was proposed in this study, calculated as an average index of all nine. Switzerland, Norway and Sweden were the countries with the highest, while Burundi, Sierra Leone and Niger were the countries with the lowest NASI scores. The deviation of each index compared with NASI was determined, resulting in GWI followed by HDI having the lowest deviation from the average rankings. The publication contribution of the scientific literature towards the three dimensions of sustainable development for each individual index was further analysed and discussed, identifying public health as one of the potential overarching indicators for sustainable development. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment